Pemberdayaan Peternak Sapi Melalui Teknologi Fermentasi Rumput Gajah Dan Daun Gamal Di Kelurahan Tambun Kabupaten Tolitoli - Mutiara Mutiara; Muhammad Fadhel A Daud; Wahyu Saputra; Aditya Ramadhan; Abd Rahman; Mukhrir Azhari NR; Nini Fitriani; Usman Usman; Ibrahim Ibrahim; Supamri Supamri; Hayatudin Hayatudin (TOLIS MENGABDI : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of cattle breeders in Tambun Village in processing local green fodder through fermentation technology. The main problems cattle breeders face are the limited availability of quality feed during the dry season and the minimal use of feed processing technology. The implementation method includes socialisation, theoretical training, practice of fermenting green fodder based on elephant grass and gamal leaves, and evaluation of fermentation results. The activity results indicate increased livestock breeders' understanding of fermentation technology, success in producing fermented products suitable for livestock, and high enthusiasm among farmers to develop independently. This activity has had a positive impact in the form of increasing human resource capacity in the livestock sector, opening up opportunities for further development through direct application in livestock maintenance and strengthening the institutionalisation of livestock breeder groups in Tambun Village.